PERAN NOTARIS DALAM UPAYA MENCIPTAKAN PERDAMAIAN PADA SENGKETA KEPEMILI'KAN SAHAM (Studi Kasus Sengketa Kepemilikan Saham PT Radio Harapan Semesta di Kota Bata,rir) - , Dwi Ajeng Sekar, Sigid Riyanto, S.H., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The objective of research was to understand and study role of notary officer in making efforts to create peace in term of shareholding lawsuit and what were problems facing the notary officer in making efforts to create peace in term of shareholding lawsuit. This research is an empirical legal study, a study which prioritized a field research to gain primary data. This empirical study focused on society behavior. To support and furnish data, a study of literatures was conducted. Furthermore, the collected data of field research and study of literatures were analyzed qualitatively. The analysis of data used inductive way of thinking, concluding results of research from things with special characteristic until a general conclusion was made. The results of research indicated that (1) Roles of notary in making efforts to create peace in term of shareholding lawsuit were mediator and facilitator by making peace deed bridging interests of parties with lawsuit to solve problems. Role of notary was to make peace deed by creation mechanism through various mediation processes such as (a) to create forum by organizing meeting schedule of parties, (b) to collect and distribute information to parties, (c) to solve lawsuit, (d) to make decision based on agreement between parties which were then included in peace deed, given peace deed as perfect proof instrument, parties whose lawsuits obtained assurance of legal certainty